2004
DOI: 10.1111/j.1365-2761.2004.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulonephritis and immunosuppression associated with dietary essential fatty acid deficiency in gilthead sea bream, Sparus aurata L., juveniles

Abstract: An experiment was conducted to determine the effect of an essential fatty acid (EFA) deficient diet on growth, immune status and renal morphology of juvenile gilthead sea bream, using two diets: a control diet containing 2% (DW) of n-3 high unsaturated fatty acid (n-3 HUFA) and a diet formulated to be deficient in EFA for this species and containing 0.5% DW of n-3 HUFA (diet NFA). After 9 weeks of feeding the EFA-deficient diet fish showed a reduction in growth compared with the control group (107.48 ± 9.14 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 49 publications
4
53
2
Order By: Relevance
“…However, in the current study except for Hb content variation between different groups, the other hematological parameters were not changed. The divergence between the present study and the above-mentioned of Montero et al (2004) might be due to the fact that n−3 LC-PUFA deficiency in silvery-black porgy did not result in anemia, as it occurred in gilthead sea bream. Lee et al (2001) also reported that dietary n−3 deficiency did not affect RBC counts, Hb and Hct parameters in rockfish (Sebastes schlegeli), which is in line with the results of current study.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…However, in the current study except for Hb content variation between different groups, the other hematological parameters were not changed. The divergence between the present study and the above-mentioned of Montero et al (2004) might be due to the fact that n−3 LC-PUFA deficiency in silvery-black porgy did not result in anemia, as it occurred in gilthead sea bream. Lee et al (2001) also reported that dietary n−3 deficiency did not affect RBC counts, Hb and Hct parameters in rockfish (Sebastes schlegeli), which is in line with the results of current study.…”
Section: Discussioncontrasting
confidence: 92%
“…In the present study, fish fed diet with 0.1% n−3 LC-PUFA showed some signs of n − 3 LC-PUFA deficiency such as decreased growth and feed utilization, a reduction in feed intake, increased HSI and alteration in the fatty acid profile of the liver. These results were similar to those already reported in other carnivorous species like gilthead seabream (Montero et al, 2004), European sea bass (Dicentrarchus labrax) (Skalli and Robin, 2004) and large yellow croaker (Larmichthys crocea) (Zuo et al, 2012). Essential fatty acid requirements of a fish species are generally correlated with dietary lipid levels, fish developmental stage and culture conditions (Glencross, 2009;NRC, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Further up the food web, EPA and DHA are important in stress resistance [30] and immunity [31] in finfish, and dietary DHA is also needed for finfish schooling behaviour [32] and growth in shellfish [29]. DHA from the marine food web is also thought to have played a critical role in human evolution [33].…”
Section: Lipid Nutritionmentioning
confidence: 99%